SISTEM ANTRIAN MODELGEO/G/1 DENGAN VACATION - Novita Eka Chandra; Supriyanto Supriyanto; Renny Renny (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2015)
Queue processes are stochastic processes which involve the arrival process and the service process. In a queue, there is a condition of servers that become unavailable for a period of time called vacation. The purpose of this research is to analyze the derivation Geo/G/1 queue systems model with vacation and its application. Furthermore, based on simulation on vacation model, with different values of traffic intensity and vacation parameter, we concluded that the bigger traffic intensity and vacation parameter values, then the mean of total number of costumers in a system and the mean of waiting time in the queue that is caused by vacation will be decreased.